2012
DOI: 10.1128/jcm.06115-11
|View full text |Cite
|
Sign up to set email alerts
|

Using Nucleic Acid Microarrays To Perform Molecular Epidemiology and Detect Novel β-Lactamases: a Snapshot of Extended-Spectrum β-Lactamases throughout the World

Abstract: The worldwide dissemination of extended-spectrum-␤-lactamase (ESBL)-and carbapenemase-producing Enterobacteriaceae is a major concern in both hospital and community settings. Rapid identification of these resistant pathogens and the genetic determinants they possess is needed to assist in clinical practice and epidemiological studies. A collection of Escherichia coli, Klebsiella pneumoniae, Klebsiella oxytoca, and Proteus mirabilis isolates, including phenotypically ESBL-positive (n ‫؍‬ 1,093) and ESBL-negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 38 publications
2
43
1
1
Order By: Relevance
“…Given this, a comprehensive approach to detect resistance genes may be appropriate for MDRE. Studies employing microarray-based molecular tests that target a large number of resistance genes suggest that such platforms may serve this role (5,(12)(13)(14)(15). Cuzon et al evaluated the Check-Points Check MDR CT103 (Check-Points Health B.V., Wageningen, The Netherlands) microarray kit by using 187 clinical isolates and reported excellent specificity (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given this, a comprehensive approach to detect resistance genes may be appropriate for MDRE. Studies employing microarray-based molecular tests that target a large number of resistance genes suggest that such platforms may serve this role (5,(12)(13)(14)(15). Cuzon et al evaluated the Check-Points Check MDR CT103 (Check-Points Health B.V., Wageningen, The Netherlands) microarray kit by using 187 clinical isolates and reported excellent specificity (16).…”
mentioning
confidence: 99%
“…cols et al, who found the Check-KPC ESBL microarray to exhibit incomplete sensitivity for these targets (13). Compared to the historical characterization of the study isolates, the new testing identified an additional 49 resistance genes (34 bla TEM , 7 bla SHV , 3 bla CMY-II , 3 bla CTX-M-9 group genes, and 2 bla CTX-M-1 group genes) in 45 isolates (46 and 48 targets detected by CT103 and CT103 XL, respectively), all of which were confirmed with conventional PCR, highlighting the added utility of microarray testing (Table 1).…”
mentioning
confidence: 99%
“…The commercially available microarray assays from Check-Points enable only the identification of genes and mutation hot spots relevant to resistance caused by ESBLs and carbapenemases, including the detection of bla KPC (4,5,7,9,22,23,44,47). However, the Check-Points system can be used as a reliable screening tool to guide PCR sequencing, allowing in this way an identification of single variants (14). The capability to identify single variants of the KPC gene might not have been a requirement in the past, as there were only a very limited number of KPC variants reported showing very similar phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…To identify all the different variants, sequencing is the gold standard, but this method is very time consuming and too demanding for routine clinical diagnostics. An alternative method is the use of a DNA microarray, which allows for rapid identification of SNPs and parallel detection of several resistance genes (4,5,7,14,15,22,23,44,47). However, the currently described methods for KPC gene detection (the Check-MDR CT101, CT102, and CT103 assays and Check-KPC extended-spectrum beta-lactamase [ESBL] microarray [Check-Points Health BV, Wageningen, Netherlands] and the hyplex SuperBug ID test system [Amplex BioSystems GmbH, Gießen, Germany]) do not allow for differentiation between the KPC variants.…”
mentioning
confidence: 99%
“…The classification of bacterial beta-lactamases is complicated. We have used the Bush (2013) system in this paper, bearing in mind that Extended Spectrum BetaLactamases (ESBLs which include TEM and SHV) and carbapenemases(such as NDM and KPC) in Gram-negatives are thought to be of the greatest clinical importance because they are difficult to treat and are relatively common in many countries [33,34]. Beta-lactamases can be Pfizer, Philadelphia, PA, USA).…”
Section: Beta-lactamase Inhibitorsmentioning
confidence: 99%